The effects of dream socialization in childhood on dream recall frequency and the attitude towards dreams in adulthood: a retrospective study - Bachner, Joachim; Raffetseder, Peter; Walz, Benedikt; Schredl, Michael (International journal of dream research, 2012)
A recent meta-analysis showed that there is a considerable gender effect, i.e., women tend to recall their dreams more often than men. Since this difference was not found for children below the age of ten, the question is whether “dream socialization” (being asked about dreaming, hearing dreams of another person) in childhood might affect dream recall in adolescence and adulthood. This hypothesis was tested in a retrospective study of 54 students. To validate the students’ estimates, the parents were also asked about the dream socialization of their children. According to the children's as well as the parents’ estimates, mother’s asking about the children’s dreams and hearing of the mother’s dreams have a significant positive effect on the dream recall frequency of the students in adulthood. In addition, the mother’s asking about their children’s dreams has a significant, positive effect on the children’s attitude towards dreams in adulthood. To establish a clear-cut causal relationship, one should conduct a longitudinal study with dream socialization being measured in the relevant period of time and a follow-up-test measuring dream recall frequency in adulthood.